IMPLEMENTATION OF PROGRESSIVE WEB APPS-BASED CLICK PROFILE ON SOCIAL MEDIA - Amin, Ruhul; Jodi, Setiawan (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2021)
Instagram as one of the social media that has active users with a high number of users is an example of the use of social media as promotional media. However, limitations on Instagram by not allowing placing a "Link" to a post cause limitations in promoting products or services. Instagram is a native app-based application found in app stores such as the Google Play Store and Apple's App Store that requires memory on a smartphone to be installed. Based on these problems the author has a desire to create an application that can be used as a medium of sharing and promotion for various types of content that can be channeled through images that are categorized into images and videos, each uploaded image can be embedded with certain "Links" using Progressive Web Apps Technology ( PWA). The goal of implementing Progress Web Application is to design and build a system that can share content with other users. The result of the implementation of PWA is to increase the number of visitors (visitors) an average of two times on content published on the website when compared to conditions before using PWA technology.